A Cocktail of Three Virulent Phages Controls Multidrug-Resistant Salmonella Enteritidis Infection in Poultry - Li, Yue; Lv, Peilin; Shi, Deshi; Zhao, Hongze; Yuan, Xu; Jin, Xiue; Wang, Xiliang (Frontiers in Microbiology, 2022)
Salmonella enterica is not only the most common pathogen of poultry and poultry-derived products but is also a significant foodborne pathogen. In recent years, many S. enterica isolates have exhibited multi-drug resistance, which places huge pressure on global economy and health. Since phages are an attractive alternative to biocontrol pathogens, we isolated a total of 15 Salmonella phages from sewage effluent, sediment, and chicken manure. The GRNsp1, GRNsp3, GRNsp6, GRNsp21, GRNsp27, GRNsp30, GRNsp50, and GRNsp51 phages exhibited a wide host range against S. enterica serovars Enteritidis and Typhimurium in vitro. In particular, GRNsp51 exerted highly efficient lytic effects against a large proportion of S. Enteritidis and S. Typhimurium strains isolated from different regions of China. Meanwhile, GRNsp8 expanded the host range of GRNsp6 and GRNsp51. Based on their host ranges and lytic capacities, GRNsp6, GRNssp8, and GRNsp51 were selected for further investigation. Morphology, one-step growth curves, and stability assays revealed that GRNsp6, GRNsp8, and GRNsp51 all belong to the Caudovirales order and display relatively short latency periods with broad pH and thermal stability. Genomic analysis indicated that the genomes of these three phages contained no genes related to virulence, antibiotic resistance, or lysogeny. In addition, we tested the effectiveness of a cocktail composed of these three phages against S. Enteritidis in a chicken model. Treatment with the oral phage cocktail 24 h before or alongside Salmonella challenge significantly reduced colonization of the intestinal tract and decreased the mRNA expression of IL-6, IFN-γ, and IL-1β in the duodenum. Together, these findings indicate that a cocktail of the GRNsp6, GRNsp8, and GRNsp51 phages could serve as an effective antimicrobial therapeutic agent against multidrug-resistant Salmonella in animal production to mitigate infections by multiple zoonotic Salmonella species.